EFFECT OF SEVERE PLASTIC DEFORMATION ON MECHANICAL AND FATIGUE BEHAVIOUR OF MEDIUM-C SHEET STEEL - Rusz, Stanislav; Hilšer, Ondřej; Ochodek, Vladislav; Čížek, Lubomir; Kraus, Martin; Mareš, Vratislav; Grajcar, Adam; Švec, Jiří (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
The DRECE method belongs to the severe plastic deformation (SPD) processes used for the refinement of sheet metal elements. A forming device used in this method is currently being installed at the workplace in the Centre of Advanced Innovation Technologies, VSB Technical University of Ostrava. In the present work structural characteristics and fracture morphology of Ck55 carbon after the application of the DRECE method with a forming tool angle of 118° are presented. The microstructure results are linked to selected mechanical properties. The tensile, hardness and fatigue tests are performed. The methodology of non-destructive residual stresses measurement in the carbon steel after extrusion and application of tensile tests on small samples are important for their use in technical practice. The paper presents the original results of selected properties after application of the DRECE method on Ck55 steel, which will be used in the future to assess the application of the DRECE method and to determine other directions of solution on this and other selected steels.